Caring for a home-dwelling older parent with mental health problems: a narrative analysis of family caregivers’ experiences - Olivia Sissil Sunde; Johanne Alteren; Siri Ytrehus (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose To gain knowledge regarding family caregivers of home-dwelling older adults with mental health problems and the meaning-making of the caregiver’s role. Design An explorative qualitative study involving narrative analysis. Methods Semi-structured individual interviews were conducted among eight adult children. Interview data were analysed using narrative analysis. The reporting adhered to consolidated criteria for reporting qualitative studies. Results Each participant narrated unique and nuanced stories of the caregiver role, but their stories also revealed prominent themes across participants’ experiences and meaning-making. The analysis revealed three themes: family relationships through a long life, a demanding and difficult caregiver role, and reconstructing the caregiver’s role by leaving the responsibility to healthcare services. Conclusion Family caregivers experienced the role as purposeful and demanding. Mostly, psychological reactions to behaviour symptoms and duration of caregiving were considered difficult and demanding. They described that they lacked knowledge of the illness and how to perform care. Sharing care responsibility with healthcare services had the potential to ease family caregivers’ burden. However, based on a long life as caregivers, some experienced difficulties when reconstructing and adjusting the role to their life situation.